The Conformity of Wage-Indexation Models with "Stylized Facts" - Fethke, Gary C. (American Economic Review, 2016)
In a recent paper, Bennett McCallum (1982) lists what he considers to be prominent empirical regularities or of aggregate economies. In particular, he notes that . . output and employment magnitudes are strongly related to contemporaneous money stock surprises, [but that] ... output and employment magnitudes are not strongly and positively related to contemporaneous price level surprises (p. 4). These facts have prompted McCallum and others to develop models of the economy where prices as well as wages are predetermined. The main feature of such models is their abandonment of aggregate-supply formulations where price level disturbances provide a channel for the real effects of money. The purpose of this paper is to demonstrate the consistency of familiar Gray and Fischer wage-indexing models and their implied aggregate-supply relationship with the stylized facts (see JoAnna Gray, 1976; Stanley Fischer, 1977). In a model where the nominal wage is indexed to the price level, the efficient use of the information conveyed by the price level imposes qualitative restrictions on the covariance matrix of disturbances. First, the correlation between the price level and innovations in the deviation of actual output from the full-information output level will be zero. Second, because the money supply contains information about real disturbances that is not conveyed by the price level, the correlation between money supply innovations and innovations in the deviation of output from the full-information level will be positive. Third, the regression of innovations in actual output on the price level will provide an estimate of the optimal degree of indexation. Evidence that is generally consistent with these properties of wage-indexation models is found in quarterly data for the five largest OECD countries. Consider the familiar aggregate formulation: 1